COMPARISON OF THE RADIOGRAPHIC AND TRACHEOSCOPIC APPEARANCE OF THE DORSAL TRACHEAL MEMBRANE IN LARGE AND SMALL BREED DOGS. Issue 6 (14th July 2015) - Lindl Bylicki, Britany J.; Johnson, Lynelle R.; Pollard, Rachel E.
Abstract : The etiology and clinical significance of increased radiographic opacity along the dorsal margin of the tracheal lumen has long been debated. Most often, this opacity is attributed to redundancy of the dorsal tracheal membrane (DTM), a condition that occurs with tracheal collapse. We hypothesized that the underlying etiology of this radiographic opacity differs between small breed dogs with tracheal collapse and small or large breed dogs without tracheal collapse. The purpose of this prospective, cross‐sectional study was to compare the radiographic appearance of an increased opacity within the trachea to tracheoscopy findings in a group of small and large breed dogs. A total of 17 small breed dogs and 16 large breed dogs were included. Of these, only one did not have a radiographically visible DTM. Small breed dogs were divided into groups with tracheal collapse ( n = 8) and those without ( n = 9) based on tracheoscopy. Tracheal collapse was absent in larger breed dogs, however both large and small breed dogs demonstrated inward invagination of the DTM. In dogs with tracheal collapse, the DTM occupied a larger percentage of the tracheal luminal height on radiographs and a larger percentage of tracheal circumference on tracheoscopy vs. dogs with an invaginated DTM on tracheoscopy and dogs with no collapse and no invagination of the DTM. Findings supported the hypothesis that increased radiographic opacity along the dorsal margin of the trachea arises from different etiologies in dogs with and without tracheal collapse.